Plastic refractory for repairing furnace lining of intermediate frequency furnace and preparation method of plastic refractory

By using alumina, mullite and modified aluminum phosphate and other materials to prepare plastics for repair of medium-frequency furnace linings, the problems of chromium pollution, strong acidity, short service life in the existing technology are solved, and high-temperature performance and heat resistance are achieved Improved shock performance and low cost, suitable for long-term storage.

CN119320280APending Publication Date: 2025-01-17ZHEJIANG YIWEI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411540316.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The existing medium-frequency furnace lining repair materials have problems such as chromium pollution, strong phosphoric acidity, short service life, short storage time, and poor high temperature performance and corrosion resistance, which are high production costs.

Method used

Use alumina, mullite and cyanite as aggregates, modified polyaluminum phosphate as bonding agents, and prepare plastics for medium-frequency furnace lining repair with plasticizer, glucose and silicon nitride, and enhance bonding through high-temperature sintering. Performance and thermal shock resistance and prolong storage time.

Benefits of technology

It realizes the low-cost preparation of plastics for repairing medium-frequency furnace linings, has excellent bonding performance, high temperature resistance, thermal shock resistance, long service life and long storage, which solves the poor bonding and use in the existing technology. Short life and short storage time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a plastic refractory for repairing a furnace lining of an intermediate frequency furnace and a preparation method thereof, and belongs to the technical field of refractory materials for intermediate frequency furnaces. The plastic refractory comprises the following components in percentage: 20%-30% of alumina, 35%-45% of mullite, 5%-15% of kyanite, 5%-10% of a plasticizer, 3%-7% of glucose, 2%-5% of silicon nitride and 10%-15% of modified aluminum polyphosphate. Wherein the modified aluminum polyphosphate is prepared by the following method: reacting aluminum polyphosphate, silica powder, polyvinyl alcohol and water at 180-220 DEG C, and cooling to room temperature to obtain the modified aluminum polyphosphate. The plastic refractory for repairing the furnace lining of the intermediate frequency furnace is low in manufacturing cost, has excellent adhesive property, high temperature resistance and thermal shock resistance, further has the advantages of long service life, long storage time and the like, and solves the problems of poor adhesive property, short service life, short storage time and the like of the plastic refractory in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials for medium frequency furnaces, and in particular to a plastic material for repairing a lining of a medium frequency furnace and a preparation method thereof. Background Art

[0002] The medium frequency furnace is a power supply device that converts 50 Hz industrial frequency AC into medium frequency (300~2000 Hz) DC. First, the three-phase industrial frequency AC is rectified and converted into DC, and then the DC is converted into an adjustable medium frequency current to supply the induction coil, generating a strong magnetic field in the energized coil, and using the principle of electromagnetic induction to heat the furnace charge. According to the principle of electromagnetic effect, the high-density magnetic lines of force generated in the induction coil can penetrate non-metallic materials and cut the metal materials contained in the induction coil, generating strong eddy currents in the metal materials, and instantly inducing heating to any metal in a non-contact form, thereby melting the metal charge (Wang Xianghui, et al. Study on the Corrosion Resistance of Ferrosilicon Slag of Refractory Materials Lining of Medium Frequency Furnace [J]. Bulletin of Silicate, 2018, 37(12): 3912-3915). The medium frequency furnace has the advantages of fast heating speed, high temperature control accuracy, high production efficiency, flexible use, and low pollution, and is widely used in metallurgy and foundry industries.

[0003] The lining of the medium frequency furnace is an important part of the medium frequency furnace. During the use of the medium frequency furnace, due to the erosion of the metal melt and slag and the thermal shock caused by frequent temperature changes, the lining will have local cracks or peeling. Damage to the lining will not only affect its performance, resulting in the failure of normal processing and smelting to achieve the desired effect, but also greatly reduce the service life of the lining and increase its maintenance and replacement costs.

[0004] The lining materials of medium frequency furnaces can be divided into three types: acidic, alkaline and neutral, corresponding to silica, magnesia, corundum (including alumina)-spinel. Correspondingly, the lining repair materials also have three types: acidic, alkaline and neutral. Among them, the neutral repair material is required to have the characteristics of strong adhesion, high temperature resistance, thermal shock resistance and erosion resistance. At present, the most widely used neutral repair material is high-alumina repair material, which mainly uses high-alumina bauxite, alumina powder and binder as raw materials, and is prepared by batching, mixing and packaging. For example, patent CN106278204 discloses a plastic material for repairing the lining of a medium frequency furnace and a preparation method thereof. The patent uses aluminum oxide powder, kyanite, chromium oxide powder, plasticizer, and alumina particles as raw materials, and phosphoric acid as a binder. After mixing, grinding, and extrusion, the plastic material for repairing the lining of a medium frequency furnace is obtained. However, the raw materials contain chromium oxide. During the preparation process of the plastic material or the subsequent repair and use of the medium frequency furnace, the exhaust gas or waste residue discharged pollutes the environment and poses a great threat to the health of humans and animals. In addition, due to the strong acidity of phosphoric acid, the repair material product using it as a binder cannot be stored for a long time. Patent CN110590345 A discloses a repair material for a medium frequency furnace and a preparation method thereof, which uses alumina, aluminum oxide powder, zirconium corundum, andalusite fine powder, and aluminum oxide micropowder as main raw materials, silica sol and zirconium sol as binders, and a small amount of titanium oxide, borax, Ti3AlC2 and other sintering promoters are added. The materials are mixed, squeezed, and packaged into a repair material, which is then applied for repair. Although this patent solves the problems of chromium pollution and phosphorus increase, it introduces components such as boron and titanium that reduce the high-temperature performance of the material, and the prices of various raw materials are expensive, resulting in poor high-temperature performance and corrosion resistance of the repair material, and high preparation costs. Summary of the invention

[0005] In view of the above deficiencies in the prior art, the present invention provides a plastic material for repairing a medium frequency furnace lining and a preparation method thereof. The plastic material for repairing a medium frequency furnace lining of the present invention has low production cost and excellent bonding performance, high temperature resistance and thermal shock resistance. In addition, it also has the advantages of long service life and long-term storage, thereby solving the problems of poor bonding, short service life and short storage time of plastic materials in the prior art.

[0006] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0007] A plastic material for repairing a medium frequency furnace lining, comprising the following components in percentages: 20% to 30% alumina, 35% to 45% mullite, 5% to 15% kyanite, 5% to 10% plasticizer, 3% to 7% glucose, 2% to 5% silicon nitride, and 10% to 15% modified aluminum polyphosphate;

[0008] The preparation method of the modified aluminum polyphosphate comprises the following steps: reacting aluminum polyphosphate, silicon powder, polyvinyl alcohol and water at 180-220°C, and cooling to room temperature to obtain modified aluminum polyphosphate.

[0009] The present invention uses alumina, mullite and kyanite as aggregates, modified aluminum polyphosphate as a binder, and adds plasticizer, glucose and silicon nitride to prepare plastic for repairing medium frequency furnace lining. The prepared plastic for repairing medium frequency furnace lining has excellent bonding performance, high temperature resistance, thermal shock resistance, and also has the advantages of long service life and long storage time. Among them, alumina and kyanite in the aggregate can be partially converted into mullite during high-temperature sintering, and finally the strength and corrosion resistance of the plastic are effectively improved. Using modified aluminum polyphosphate as a binder and glucose can enhance the bonding performance of the plastic for repairing medium frequency furnace lining and extend its shelf life. Glucose will be carbonized after high-temperature sintering, and the carbonization product will form a complex with silicon and aluminum in the plastic to further enhance the mechanical properties of the plastic. Silicon nitride forms nitrogen at high temperature, which can reduce the erosion of the repair material by the metal liquid, so that a higher number of furnaces can be used.

[0010] Preferably, the mass ratio of the aluminum polyphosphate, silicon powder, polyvinyl alcohol and water is 10:(2-4):(0.5-1.5):(100-200).

[0011] Preferably, the polyaluminum phosphate includes one or more of aluminum tripolyphosphate, aluminum tetrapolyphosphate, and high polyaluminum phosphate.

[0012] Preferably, the average particle size of the silicon powder is 0.1-0.5 μm, and the content of SiO2 is greater than 90%.

[0013] Preferably, the polyvinyl alcohol is polyvinyl alcohol 17-88 and / or polyvinyl alcohol 17-99.

[0014] Preferably, the particle size of the alumina is ≤3 mm.

[0015] Preferably, the particle size of the mullite is ≤5 mm.

[0016] Preferably, the particle size of the kyanite is ≤3 mm.

[0017] Preferably, the plasticizer is a mixture of bentonite and sodium lignin sulfonate, and the mass ratio of bentonite to sodium lignin sulfonate is 1:(5-10).

[0018] The method for preparing the plastic material for repairing the intermediate frequency furnace lining comprises the following steps:

[0019] Weigh each component in proportion; mix alumina, mullite, kyanite, glucose, silicon nitride and 50% of the total amount of modified polyaluminum phosphate evenly, and then add the remaining modified polyaluminum phosphate and plasticizer, mix evenly to obtain the plastic material for repairing the lining of the medium frequency furnace.

[0020] When the plastic material for repairing the lining of a medium frequency furnace is used, a proper amount of the plastic material is taken, molded into any shape, adhered to the position to be repaired, and sintered at 1100-1300°C.

[0021] Compared with the prior art, the present invention is beneficial in that:

[0022] (1) The present invention uses alumina, mullite and kyanite as aggregates, modified aluminum polyphosphate as a binder, and adds plasticizer, glucose and silicon nitride to prepare a plastic material for repairing a medium frequency furnace lining. The prepared plastic material for repairing a medium frequency furnace lining has excellent bonding performance, high temperature resistance, thermal shock resistance, and also has the advantages of long service life and long storage time.

[0023] (2) The present invention uses aluminum polyphosphate, silicon powder and polyvinyl alcohol as raw materials to prepare modified aluminum polyphosphate, which is used as a binder to prepare plastics, which can effectively improve the high temperature resistance and thermal shock resistance of the plastics; in addition, the modified aluminum polyphosphate is used in combination with an additive, glucose, to improve the bonding performance and shelf life of the plastics. When the plastics are stored in a sealed container, the shelf life is longer than that of similar products in the prior art;

[0024] (3) The plastic material of the present invention has simple preparation steps and low preparation cost, which is conducive to industrial-scale production. DETAILED DESCRIPTION

[0025] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The present invention provides a plastic material for repairing a medium frequency furnace lining, comprising the following components in percentages: 20% to 30% alumina, 35% to 45% mullite, 5% to 15% kyanite, 5% to 10% plasticizer, 3% to 7% glucose, 2% to 5% silicon nitride, and 10% to 15% modified aluminum polyphosphate;

[0027] The preparation method of the modified aluminum polyphosphate comprises the following steps: reacting aluminum polyphosphate, silicon powder, polyvinyl alcohol and water at 180-220°C, and cooling to room temperature to obtain modified aluminum polyphosphate.

[0028] In some examples, the mass ratio of the aluminum polyphosphate, silicon micropowder, polyvinyl alcohol, and water is 10:(2-4):(0.5-1.5):(100-200).

[0029] In some examples, the polyaluminum phosphate includes one or more of aluminum tripolyphosphate, aluminum tetrapolyphosphate, and high polyaluminum phosphate.

[0030] In some examples, the polyvinyl alcohol is polyvinyl alcohol 17-88 and / or polyvinyl alcohol 17-99.

[0031] In some examples, the plasticizer is a mixture of bentonite and sodium lignin sulfonate, and the mass ratio of bentonite to sodium lignin sulfonate is 1:(5~10).

[0032] In the following specific embodiments, the aluminum polyphosphate is aluminum tripolyphosphate; the average particle size of the silicon micropowder is 0.1~0.5 μm, and the content of SiO2 is greater than 90%; the polyvinyl alcohol is polyvinyl alcohol 17-88; the particle size of the alumina is ≤3 mm; the particle size of the mullite is ≤5 mm; the particle size of the kyanite is ≤3 mm; the plasticizer is a mixture of bentonite and sodium lignin sulfonate, and the mass ratio of the bentonite to the sodium lignin sulfonate is 1:10.

[0033] Example 1

[0034] A plastic material for repairing a medium frequency furnace lining, the preparation steps are as follows:

[0035] (1) reacting aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water at 200°C for 4 hours, and cooling to room temperature to obtain modified aluminum polyphosphate; the mass ratio of aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water is 10:2:1.5:100;

[0036] (2) Weigh each component in proportion, mix 20% alumina, 45% mullite, 10% kyanite, 5% glucose, 5% silicon nitride and 5% modified aluminum polyphosphate in a mixer, and put them into a sealed container to seal the materials; then add 5% modified aluminum polyphosphate and 5% plasticizer, mix well to obtain plastic material for repairing medium frequency furnace lining.

[0037] Example 2

[0038] A plastic material for repairing a medium frequency furnace lining, the preparation steps are as follows:

[0039] (1) reacting aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water at 180°C for 4 hours, and cooling to room temperature to obtain modified aluminum polyphosphate; the mass ratio of aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water is 10:4:0.5:200;

[0040] (2) Weigh each component in proportion, mix 30% alumina, 35% mullite, 10% kyanite, 5% glucose, 5% silicon nitride and 5% modified aluminum polyphosphate in a mixer, and put them into a sealed container to seal the materials; then add 5% modified aluminum polyphosphate and 5% plasticizer, mix well to obtain plastic material for repairing medium frequency furnace lining.

[0041] Example 3

[0042] A plastic material for repairing a medium frequency furnace lining, the preparation steps are as follows:

[0043] (1) reacting aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water at 220° C. for 4 h, and cooling to room temperature to obtain modified aluminum polyphosphate; the mass ratio of aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water is 10:3:1.5:150;

[0044] (2) Weigh each component in proportion, mix 25% alumina, 40% mullite, 10% kyanite, 5% glucose, 5% silicon nitride and 5% modified aluminum polyphosphate in a mixer, and put them into a sealed container to seal the materials; then add 5% modified aluminum polyphosphate and 5% plasticizer, mix well to obtain plastic material for repairing medium frequency furnace lining.

[0045] Comparative Example 1

[0046] A plastic material for repairing a medium frequency furnace lining, the preparation steps are as follows:

[0047] (1) reacting aluminum polyphosphate, polyvinyl alcohol and water at 200° C. for 4 h, and cooling to room temperature to obtain modified aluminum polyphosphate; the mass ratio of aluminum polyphosphate, polyvinyl alcohol and water is 10: 1.5: 100;

[0048] (2) Weigh each component in proportion, mix 20% alumina, 45% mullite, 10% kyanite, 5% glucose, 5% silicon nitride and 5% modified aluminum polyphosphate in a mixer, and put them into a sealed container to seal the materials; then add 5% modified aluminum polyphosphate and 5% plasticizer, mix well to obtain plastic material for repairing medium frequency furnace lining.

[0049] Comparative Example 2

[0050] A plastic material for repairing a medium frequency furnace lining, the preparation steps are as follows:

[0051] (1) reacting aluminum polyphosphate, silicon micropowder and water at 200°C for 4 hours, and cooling to room temperature to obtain modified aluminum polyphosphate; the mass ratio of aluminum polyphosphate, silicon micropowder and water is 10:2:100;

[0052] (2) Weigh each component in proportion, mix 20% alumina, 45% mullite, 10% kyanite, 5% glucose, 5% silicon nitride and 5% modified aluminum polyphosphate in a mixer, and put them into a sealed container to seal the materials; then add 5% modified aluminum polyphosphate and 5% plasticizer, mix well to obtain plastic material for repairing medium frequency furnace lining.

[0053] Comparative Example 3

[0054] A plastic material for repairing a medium frequency furnace lining, the preparation steps are as follows:

[0055] (1) mixing aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water at room temperature to obtain a mixture; the mass ratio of aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water is 10: 2: 1.5: 100;

[0056] (2) Weigh each component in proportion, mix 20% alumina, 45% mullite, 10% kyanite, 5% glucose, 5% silicon nitride and 5% mixed material in a mixer, and put them into a sealed container to trap the materials; then add 5% mixed material and 5% plasticizer, mix well to obtain plastic material for repairing medium frequency furnace lining.

[0057] Performance Testing

[0058] (1) Adhesion performance test: The plastics of Examples 1 to 3 and Comparative Examples 1 to 3 were placed on glass plates respectively, and were pressed into a round cake shape on the glass plates with a wooden hammer. The glass plates were placed vertically, and the falling time of the round cake-shaped plastics was recorded. The longer the time, the greater the bonding strength of the plastics. The test results are shown in Tables 1 and 2.

[0059] (2) Storage time test: The plastic materials of Examples 1 to 3 were placed in sealed plastic bags and checked every day to see if they were hardened and failed. The hardening and failure time of the plastic materials was recorded. The test results are shown in Table 1.

[0060] (3) Bulk density and strength performance test: The plastics of Examples 1 to 3 and Comparative Examples 1 to 3 were placed in a cylindrical mold and pounded 20 times in both directions using a hammer sample making machine to prepare Φ50×50 mm cylindrical specimens; the cylindrical specimens were dried at 110°C for 24 h, and then calcined at 1100°C and 1600°C for 3 h, respectively. The radial line change was tested according to GB / T5988-2007, the bulk density was tested according to GB / T2997-2015, and the room temperature compressive strength was tested according to GB / T5072-2008. The test results are shown in Tables 1 and 2.

[0061] (4) Furnace age test: The plastic materials of Examples 1 to 3 and Comparative Examples 1 to 3 were tested for furnace age in a 15 t medium frequency furnace. The test results are shown in Tables 1 and 2.

[0062] (5) Maximum use temperature test: Take an appropriate amount of the plastic material of Examples 1 to 3, shape it into any shape and adhere it to the position to be repaired. After sintering at 1300°C, gradually increase the temperature and observe the changes in the repaired position. The test results are shown in Table 1.

[0063] Table 1: Performance test results of plastics prepared in Examples 1 to 3

[0064]

[0065] As shown in Table 1, the present invention uses alumina, mullite, and kyanite as aggregates, modified aluminum polyphosphate as a binder, and adds plasticizers, glucose, and silicon nitride to prepare a plastic material for repairing a medium frequency furnace lining. The prepared plastic material for repairing a medium frequency furnace lining has a bulk density of 2.6-2.8 g / cm after drying at 110°C for 24 h. 3 , flexural strength greater than 15 MPa; bulk density after sintering at 1100℃×3 h is 2.8~3.0 g / cm 3 , flexural strength is greater than 16 MPa, linear change rate is less than 1.5%; bulk density after sintering at 1600℃×3 h is 2.9~3.1 g / cm 3 , flexural strength is greater than 16 MPa, and the linear change rate is less than 1%; the maximum use temperature of the plastic material for repairing the intermediate frequency furnace lining of the present invention can reach 1700°C; after repair, it can be used for 40~50 furnaces.

[0066] Table 2: Performance test results of plastics prepared in Comparative Examples 1 to 3

[0067]

[0068] It can be seen from Table 2 that the plastic materials for repairing the medium frequency furnace lining prepared in Comparative Examples 1 to 3 have poor bonding properties, low volume density, large linear change rate, and low flexural strength, and can only be used for a maximum of 25 furnaces after repair.

[0069] In summary, the present invention uses alumina, mullite and kyanite as aggregates, modified aluminum polyphosphate as a binder, and synergistically combines plasticizers, glucose and silicon nitride to prepare plastic materials for repairing medium frequency furnace linings. The plastic materials of the present invention have low production costs and excellent bonding properties, high temperature resistance and thermal shock resistance. In addition, they also have the advantages of long service life and long-term storage, which solves the problems of poor bonding, short service life and short storage time of plastic materials in the prior art.

[0070] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A plastic material for repairing a medium frequency furnace lining, characterized in that: The composition includes the following percentages: alumina 20%~30%, mullite 35%~45%, kyanite 5%~15%, plasticizer 5%~10%, glucose 3%~7%, silicon nitride 2%~5%, and modified polyaluminum phosphate 10~15%; The preparation method of the modified aluminum polyphosphate comprises the following steps: reacting aluminum polyphosphate, silicon powder, polyvinyl alcohol and water at 180-220°C, and cooling to room temperature to obtain modified aluminum polyphosphate.

2. The plastic material for repairing the lining of a medium frequency furnace according to claim 1, characterized in that: The mass ratio of the aluminum polyphosphate, silicon micropowder, polyvinyl alcohol and water is 10:(2-4):(0.5-1.5):(100-200).

3. The plastic material for repairing the lining of a medium frequency furnace according to claim 1, characterized in that: The polyaluminum phosphate includes one or more of aluminum tripolyphosphate, aluminum tetrapolyphosphate, and high polyaluminum phosphate.

4. The plastic material for repairing the lining of a medium frequency furnace according to claim 1, characterized in that: The particle size of the silicon micropowder is 0.1-0.5 μm, and the content of SiO2 is greater than 90%.

5. The plastic material for repairing the lining of a medium frequency furnace according to claim 1, characterized in that: The reaction time is 4 to 6 h.

6. The plastic material for repairing the lining of a medium frequency furnace according to claim 1, characterized in that: The particle size of the alumina is ≤3 mm.

7. The plastic material for repairing the lining of a medium frequency furnace according to claim 1, characterized in that: The particle size of the mullite is ≤5 mm.

8. The plastic material for repairing the lining of a medium frequency furnace according to claim 1, characterized in that: The particle size of the kyanite is ≤3 mm.

9. The plastic material for repairing the lining of a medium frequency furnace according to claim 1, characterized in that: The plasticizer is a mixture of bentonite and sodium lignin sulfonate, and the mass ratio of the bentonite to the sodium lignin sulfonate is 1:(5-10).

10. A method for preparing a plastic material for repairing a medium frequency furnace lining as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Weigh each component in proportion; S2. Evenly mix alumina, mullite, kyanite, glucose, silicon nitride and 50% of the total amount of modified aluminum polyphosphate to form a mixed material; then add the remaining modified aluminum polyphosphate and plasticizer, mix evenly to obtain a plastic material for repairing a medium frequency furnace lining.

Citation Information

Patent Citations

  • Repair material for intermediate frequency furnace and preparation method of repair material

    CN110590345A

Cited By

  • Calcium hexaaluminate repairing material as well as preparation method and application thereof

    CN120682040A

  • Phosphate combined refractory repair material and preparation method thereof

    CN121651896A